Visual soil structure quality and its correlation to quantitative soil physical properties of upland rice site in Falcataria moluccana agroforestry system (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Briliawan BD, Wijayanto N, Wasis B. 2022. Visual soil structure quality and its correlation to quantitative soil physical properties of upland rice site in Falcataria moluccana agroforestry system. Biodiversitas 23: 1894-1903. Sengon and upland rice are plants that have the potential to be combined in the agroforestry system. However, its development often results in poor quantitative soil physical properties. Measuring the soil’s physical properties is expensive and complicated to do by some people. This study aims to measure the visual soil structure quality from different land covers and calculate its correlation to the parameters of the soil’s physical properties. The research was conducted in the Cikabayan forest and used the purposive sampling method to take soil samples. The research was conducted by comparing nine land covers in the form of agroforestry and monoculture developed in organic and conventional agriculture with tropical rainforests as natural vegetation. Three samples were taken for each land cover type and analyzed with a completely randomized design. The research showed that the vegetation of tropical rainforest generated the best score on all visual soil structure quality measurement methods (VESS, GrassVESS Sq and GrassVESS Rm). The measurement of soil physical properties at natural vegetation of tropical rainforests generated the highest score on the porosity (57.303%). Meanwhile, monoculture-conventional land generated the highest bulk density (1.373 g.cm-3). The VESS method had the highest correlation with soil physical properties compared to other visual soil structure quality measurement methods. Thus, natural vegetation is the best type of land cover compared to all cultivated land and the VESS method is the most appropriate method for estimating soil physical properties.
Keywords: Bulk density, GrassVESS Rm, GrassVESS Sq, porosity, VESS